Modified Student Psychology Based Optimization Algorithm for Economic Dispatch Problems. Issue 15 (15th December 2021) - Basu, Subhamay; Basu, Mousumi
ABSTRACT: This manuscript develops and suggests modified student psychology-based optimization (MSPBO) algorithm to the convoluted economic dispatch problem. The psychology of the students who provide more attempts to perk up their recital in the exam equal to the echelon for turn out to be the best student in the class forms the basis of student psychology-based optimization (SPBO) algorithm. In this manuscript, MSPBO has been suggested to improve convergence speed and better-quality solutions. The efficacy of MSPBO algorithm has been divulged on five different economic dispatch problems incorporating valve-point consequence, proscribed feasible area, ramp rate borders, and manifold fuels. Simulation outcomes of the recommended method are matched up toward those attained as of other affirmed artificial intelligence methods. It is viewed from the assessment that suggested MSPBO is capable of giving better results.